Heat generation measurement and thermal management with phase change material based on heat flux for high specific energy power battery. (25th July 2021) - Wang, Haimin; Wang, Yufei; Hu, Feng; Shi, Weijie; Hu, Xuebin; Li, Huanqi; Chen, Si; Lin, Hao; Jiang, Chenglong
Highlights: The built-in thermocouple is used to measure the central temperature of a cell. A heat flux sensor is used to measure the heat dissipation of the cell directly. PCMs are designed with measured heat flux to manage the temperature of the cell. The distance between two adjacent cells obviously affects their own temperature. The heat flux is used to monitor the solid state of PCMs. Abstract: LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) lithium-ion battery is a kind of high specific energy power battery. By directly measuring the heat flux on the surface of a 21700-type cylindrical battery and the temperature of its inner center, the heat generation rate, the heat energy dissipated and the electric energy released at different discharge rates are all obtained. The results turn out that increasing the discharge rate will reduce the electric energy and correspondingly increase the heat energy released, while the total amount of both remains unchanged. When the discharge rate increases from 1C to 2.5C, the ratio of discharge heat generation to discharged energy increases from 2.89% to 7.89%. According to the heat generation rate obtained from the experimental results, a single cylindrical cell structure and hexagonal cell module were designed for different discharge rates with high thermal conductivity graphene paraffin composite phase change material (PCM). PCM structure can well manage the thermal parameters, which helps to maintain the stability and consistency of battery temperature. The distance between two adjacent batteries has a greater impact on the temperature distribution of the battery module during high rate discharge, and monitoring the change of heat flux can predict the failure of the thermal management of the battery in advance. It is a beneficial attempt to adopt PCM to manage the temperature field of the battery pack and use heat flux to monitor the solid state of PCM, which is also very helpful for the safe operation of the battery system.